2012
DOI: 10.3109/09546634.2012.697990
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual assessments versus planimetry assessments in a large-scale clinical trial of onychomycosis

Abstract: The results suggest that objective measures such as planimetry will reduce the impact of visual assessment errors, and techniques to increase the standardization of onychomycosis assessment are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…9,11,14 Also, from our experience, our patients would not have tolerated higher fluence because of significant discomfort at the fluences used (6-8 J/cm 2 ). The absence of planimetry to measure the primary outcome is also a limitation but, as evaluated in the study by Gupta and Cooper, 15 comparison showed good statistical agreement of visual and planimetry measures.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,14 Also, from our experience, our patients would not have tolerated higher fluence because of significant discomfort at the fluences used (6-8 J/cm 2 ). The absence of planimetry to measure the primary outcome is also a limitation but, as evaluated in the study by Gupta and Cooper, 15 comparison showed good statistical agreement of visual and planimetry measures.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, onychomycosis severity and follow‐up of clinical evolution of in treated patients could be quantified using an image analysis program. To reduce errors using the visual estimation when determining onychomycosis treatment efficacy, 17‐19 several methods have been previously described 20,21 . However, they are time consuming or require access to sophisticated software, rarely available for dermatologists who deal with onychomycosis in routine.…”
Section: Discussionmentioning
confidence: 99%
“…History and clinical evaluation are not sufficient to make the diagnosis of onychomycosis, and empiric treatment of presumed onychomycosis may lead to lower than expected cure rates and missed diagnoses. A diagnosis based solely on physical examination/clinical signs can be incorrect, and various laboratory assessments would be useful for confirmation …”
Section: Differential Diagnosis Of Onychomycosismentioning
confidence: 99%